Directing scenes and senses : The thinking of Regie - Boenisch, Peter M. (Book collections on Project MUSE., 2015)
Explores the thinking of Regie, the Continental European tradition of staging playtexts, as a meeting between Continental theater and philosophy. Develops new perspectives on the cultural history of Regie through historical and contemporary manifestations in German, Dutch, and Flemish theater.